Biochemical interaction of the Escherichia coli RecF, RecO, and RecR proteins with RecA protein and single-stranded DNA binding protein. - Umezu, K (1993)
The Escherichia coli RecF, RecO, and RecR proteins were analyzed for their effect on RecA-mediated pairing of single-stranded circular DNA and homologous linear duplex DNA substrates. As shown by other workers, joint molecule formation by RecA was inhibited by E. coli single-stranded DNA binding protein (SSB) when it was added to single-stranded DNA before RecA. This inhibitory effect was overcome by the addition of RecO and RecR or RecF, RecO, and RecR. Both the rate and extent of joint molecule formation were restored to the maximal level observed when SSB was added after RecA. RecF, RecO, and RecR proteins had no effect on the conversion of joint molecules to final products and only appeared to stimulate an early step in the pairing reaction. The stimulatory effect of RecF, RecO, and RecR was not seen without SSB or when SSB was added after RecA. RecF protein by itself inhibited reactions in mixtures containing RecA and SSB, and this inhibition was overcome by the addition of RecO and RecR. These data suggest that RecO and RecR, and possibly RecF, help RecA overcome inhibition by SSB and utilize SSB-single-stranded-DNA complexes as substrates.